2004
DOI: 10.1097/01.nmd.0000131913.94916.d5
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Psychiatric Disorder Among a Community Sample of Crack Cocaine Users

Abstract: The Diagnostic Interview Schedule for DSM-IV was used to assess the lifetime prevalence of psychiatric disorder among not-in-treatment crack cocaine users (N = 313). The most common dependencies involved cocaine (59.7%), alcohol (37.7%), and cannabis (12.1%). The most common nondependency disorders were antisocial personality disorder (ASPD; 24%), depression (17.8%), and posttraumatic stress disorder (PTSD; 11.8%). Comorbidity was present in 36.4% of the sample. Proportionately more white than black users were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
65
0
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 17 publications
11
65
0
13
Order By: Relevance
“…Given that the overwhelming majority of participants in the Ohio and Kentucky samples were white, while the majority in the Arkansas sample was African American, the result is consistent with an evolving literature that suggests white drug users are more likely to manifest mental health problems than are African American drug users (Falck et al, 2004;Compton et al, 2000). The reasons underlying this phenomenon are uncertain, but the finding has emerged again, this time in a multi-site community sample of rural drug users.…”
Section: Discussionsupporting
confidence: 69%
“…Given that the overwhelming majority of participants in the Ohio and Kentucky samples were white, while the majority in the Arkansas sample was African American, the result is consistent with an evolving literature that suggests white drug users are more likely to manifest mental health problems than are African American drug users (Falck et al, 2004;Compton et al, 2000). The reasons underlying this phenomenon are uncertain, but the finding has emerged again, this time in a multi-site community sample of rural drug users.…”
Section: Discussionsupporting
confidence: 69%
“…Psychological symptoms that occur after chronic use include somatic problems (Johanson et al 1999;Watson et al 1992), eating disorders (Ross-Durow and Boyd 2000), anxiety and depression (Beckwith et al 1999;Falck et al 2002). Associations between chronic cocaine use and conditions such as obsessive-compulsive disorder (Crum and James 1993), paranoia (Espinosa et al 2001;Lejoyeux et al 2000), schizophrenia (Bowers et al 2001), and antisocial personality disorder (Falck et al 2004;Ladd and Nancy 2003) have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Bennett and colleagues 5 found that maternal self-report of harsh discipline, depressive symptoms, and a composite variable of environmental risk significantly predicted CBCL externalizing problems while maternal depression predicted CBCL internalizing problems at age 4. Considering the high rate of comorbidity between depression and crack cocaine use found in community-based samples, 13,14 it is not surprising that studies of children with PCE have found an association between maternal depression and report of child behavior problems.…”
mentioning
confidence: 99%